Empirical study on urban sustainable development model based on identification of advantages and disadvantages - Zhang, Lili; Su, Di; Guo, Wenhao; Li, Siyao (Frontiers in Sustainable Cities, 2022)
Promoting the sustainable development of cities and unifying ecological, economic, and social benefits are of great significance to the long-term development of the country. Taking the macro level as the starting point, this paper constructs a hierarchical identification model of urban personality advantage characteristics from the perspective of sustainable development. To identify, classify and compare the sustainable urban development models, SPSS was used to analyze the weights of the dominant characteristics of various cities in China. First, according to the identification model, the individual advantages of each city are identified hierarchically; Secondly, all feature weights are clustered, and finally, the sustainable development patterns of different cities are discussed according to the clustering results, and relevant countermeasures are proposed. The comparison shows that each city has its advantages and disadvantages in sustainable development, and these cities have not been able to implement the concept and policies of sustainable development well. Given these problems, this paper recommends grasping the main force, gradually solving and improving the weaker links in sustainable development, and reducing the imbalance in development. In the context of sustainable development strategies, the development of Chinese cities in a virtuous circle is of great significance.